Screening of antibiotic residue in transported live fish and water collected from different fish markets in Mymensingh district of Bangladesh - Hasan, Md Mehedi; Rafiq, Kazi; Ferdous, Most Rifat Ara; Hossain, Md Tarek; Ripa, Arifa Parvin; Haque, Shahroz Mahean (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: The objective of this study was to evaluate the persistence of oxytetracycline (OTC) residue in common fish species (Catla, Rui, Mrigal, and Pangas) available in local fish markets and the corresponding transport water of the Mymensingh region. Materials and Methods: Live fish and corresponding transport water samples were analyzed by thin layer chromatography (TLC) and high-performance liquid chromatography for qualitative and quantitative detection of OTC residue,respectively. A total of 240 fish samples and 60 watersamples were randomly collected from three local fish markets during the summer and winter seasons. Results: OTC residues were detected in 18 samples (13 fish and 5 water samples) in the summer and 8 samples (only fish samples) in the winter. The overall percentage of antibiotic residue positive in fish samples was 5.42%, and in water samples, it was 8.33%. In fish, OTC concentrations of TLC-positive samples ranged from 34.7 to 56.85 parts per billion (ppb) in Catla, 23.45–35.37 in Rui, 11.02–26.80 in Mrigal, and 10.80–77.55 in Pangas during summer. The concentrations were 18.5 ppb in Catla, 15–16.09 in Rui, 10–14.63 in Mrigal, and 21.02–40.11 in Pangas during the winter season. On the other hand, the range of OTC concentrations of TLC-positive samples for water was 12.9–59.18 ppb during summer and below the detection level during winter. The highest prevalence of antibiotic residues among fish samples was found in Pangas (16.67%). The highest percentage of samples (15% in the fish sample and 30% in the water sample) found to be positive were collected from Mechua Bazar. The comparison between the summer and winter seasons showed that the percentage of positive antibiotic residue in the summer season (10.38% for fish and 16.67% for water) is higher than that of the winter season (6.67% for fish samples only). This variation indicates that fish transporters use more antibiotics during the summer than in the winter season. The difference between the means of fish species and water samples was not statistically significant (p > 0.05). In addition, no samples exceeded the maximum residue limits (MRL) of OTC (100 ppb) in fish set by the European Commission. Conclusion: Although the concentrations of antibiotic residues in fish edible tissues are below MRL values, the presence of antibiotic residuesin transported water may lead to the development of antimicrobial resistance bacteria that are detrimental to humans, animals, and aquatic animals. J. Adv. Vet. Anim. Res., 9(1): 104–112, March 2022 http://doi.org/10.5455/javar.2022.i574